2015
DOI: 10.3389/fnagi.2015.00024
|View full text |Cite
|
Sign up to set email alerts
|

‘Kitchen and cooking,’ a serious game for mild cognitive impairment and Alzheimer’s disease: a pilot study

Abstract: Recently there has been a growing interest in employing serious games (SGs) for the assessment and rehabilitation of elderly people with mild cognitive impairment (MCI), Alzheimer’s disease (AD), and related disorders. In the present study we examined the acceptability of ‘Kitchen and cooking’ – a SG developed in the context of the EU project VERVE (http://www.verveconsortium.eu/) – in these populations. In this game a cooking plot is employed to assess and stimulate executive functions (such as planning abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 41 publications
7
151
0
5
Order By: Relevance
“…Os treinamentos realizados variaram de duas a 24 semanas de duração com um total de uma a 60 sessões. Em um dos estudos não foi localizado o delineamento referente ao número e duração das sessões na semana (Manera et al, 2015). Com relação aos jogos utilizados, dos doze estudos, oito utilizaram jogos da categoria JTC, três da categoria JDE e um comparou os efeitos de jogos de ambas as categorias (Zimermann et al, 2014).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Os treinamentos realizados variaram de duas a 24 semanas de duração com um total de uma a 60 sessões. Em um dos estudos não foi localizado o delineamento referente ao número e duração das sessões na semana (Manera et al, 2015). Com relação aos jogos utilizados, dos doze estudos, oito utilizaram jogos da categoria JTC, três da categoria JDE e um comparou os efeitos de jogos de ambas as categorias (Zimermann et al, 2014).…”
Section: Resultsunclassified
“…Dentro dos transtornos neurocognitivos, observou-se que os aprimoramentos foram superiores nos idosos acometidos por DCL, seguido pela demência e por fim, os menores níveis de aprimoramento foram observados em idosos nos estágios inicias de DA (Bamidis et al, 2015;Manera et al, 2015). Contudo, embora estes aprimoramentos sejam encontrados em menores proporções, devido à gravidade da patologia instaurada, eles foram superiores a outras formas de intervenções as quais não utilizaram jogos eletrônicos (Bamidis et al, 2015;Fernandez-Calvo et al, 2011).…”
Section: Quais Os Efeitos Dos Jogos Eletrônicos Na Cognição De Idososunclassified
See 1 more Smart Citation
“…Results from recent studies have shown that several stimulation-oriented ICT could likely improve affective affects, such as using serious games on tablet showing interest for apathetic individuals (Manera et al, 2015) or exergame showing increased positive emotions and interest (Ben-Sadoun et al, 2016). In various medical situations, the use of commercial video games for rehabilitation showed similar results compared to conventional rehabilitation methods but increased patients’ motivation (Bonnechère et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The applications of serious games have been restricted to rehabilitation for enhancing cognitive and physical function in different disorders with EDF, such as Alzheimer's disease, mild cognitive impairment [91][92][93][94][95][96][97][98][99] and treatment of mental health disorders [100].…”
Section: Neuropsychological Assessment In Simulated Environmentsmentioning
confidence: 99%